ELECTRONIC NOSE A NOVEL TOOL FOR QUALITY AND PROCESS CONTROL IN THE FOOD INDUSTRY - QUICAZÁN S., Martha C.; DÍAZ M., Amanda C.; ZULUAGA D., Carlos M. (Vitae, 2011)
Electronic nose systems, more commonly known in the food industry as electronic noses, are considered nowadays as an analytical technique with wide applicability. This is a non-destructive technique designed to analyze, recognize and identify very low levels of chemical volatile substances. An array of electrochemical sensors creates a unique digital fingerprint of the food, enabling quality control, product development, characterization, classification and origin identification, maturity stage, assessment of shelf-life and as a tool of control to identify problems that threaten the market, such as counterfeiting and adulteration. This paper reviewed the literature of the last 10 years on the basic principle of operation of an electronic nose: the components used in its operation such the sensor system and the processing information system obtained by using multivariate statistical techniques and artificial intelligence. Electronic nose data so obtained were objective, reproducible, reliable and acquired in real time. Sensors identify volatile compounds by functional groups and through statistical analysis techniques guarantee their usefulness in different industrial applications.